PERSEPSI MASYARAKAT DESA TERHADAP AKUNTABILITAS PENGELOLAAN KEUANGAN DESA DI DESA LAMAHALA JAYA KECAMATAN ADONARA TIMUR, KABUPATEN FLORES TIMUR - Maryono; Nurcahyat Abdurahman; herni Sunarya (PROGRAM STUDI AKUNTANSI - UNIVERSITAS MUHAMMADIYAH KUPANG, 2020)
This study aims to find out the perceptions of the village community on accountability in the planning, implementation and reporting of village financial management in Lamahala Jaya Village, East Adonara District, East Flores Regency. The type of research used in this study is quantitative research using a descriptive approach. Data obtained from questionnaires / interviews, interviews, and documentation. The sample used was 60 respondents who were taken based on the sampling technique by means of